Wiara i przemoc - Karol Tarnowski (Jesuit University Ignatianum in Krakow, 2017)
The author undertakes phenomenological deliberations referring to the relationship between faith and violence and attempts to reveal the "mechanism" which makes that power and faith change into a "believing power". Power may yield to temptation of ruling, abusing itself in the act of being exhilarated by itself. The power of some people may also delude with the prospect of unlimited ability to rule over the autonomy of others. Since it is not possible to rule over another person fully, due to the sphere of freedom present in this person, violence must make use of fear. Such processes of delusion and intimidation are realized in ideologies, reaching even metaphysical justifications of fear: up till the argument of God of violence. The source of experience of faith is pre-trust, the affirmative clinging on to the truth, opening a kind of pre-hope. Faith refers to a kind of reality, but it is given through intentional thought constructs, through content: religious and cultural specifications, through gnosis which provides certainty. These are its external truths. Their contents state personalities. They attract emotionally, as embodiments of hope and truth of faith which is to order life according to the expected sense, which will allow to control its meaninglessness. This is delusion, which still does not eliminate falsehood or violence ... Therefore man has to protect his faith by thinking towards the ethos of internal truth of faith. Towards the affirmation of existence as such, which feeds on thinking faith and as a result caring about man's dignity.